Ururau: a free and open-source discrete event simulation software. Issue 4 (1st November 2017) - Peixoto, Túlio Almeida; de Assis Rangel, João José; de Oliveira Matias, Ítalo; da Silva, Fábio Freitas; Tavares, Eder Reis
Abstract: This paper has the purpose of describing the architecture and operation of Ururau, a software used to create discrete event simulation models based on the Java Simulation Library. Ururau is a free and open-source multiplatform software, which allows the user to develop models in the graphical interface or implement them directly in the source code. This characteristic allows the user to employ it as a tool for modeling and simulation of discrete event systems and also as a learning tool. Thus, an experienced modeler can add specific algorithms to simulation models or new features to the simulator. Also, with access to the source code, a beginner modeler can understand the internal structure of a discrete event simulation software. Initial results have demonstrated this new software's ability in building small and simple models efficiently.